Provision of Reproductive Healthcare to Women with Disabilities: A Survey of Obstetrician?Gynecologists' Training, Practices, and Perceived Barriers - Laura H. Taouk; Laura H. Taouk; Michael F. Fialkow; Jay A. Schulkin; Jay A. Schulkin (Mary Ann Liebert, 2018)
Purpose: The purpose of this study was to document current awareness, attitudes, and training regarding the care of women with disabilities by obstetrician?gynecologists (ob-gyns) and explore barriers that may explain observed discrepancies in care. Methods: One thousand ob-gyns, including 500 members of the Collaborative Ambulatory Research Network (CARN), were surveyed on practice accessibility, training, awareness, barriers, beliefs, comfort, challenges, practices, contraceptive counseling, and preconception/pregnancy counseling. Results: CARN, 49.0%, and non-CARN, 19.4%, members completed the survey for an overall response rate of 33.9%. Most respondents indicated feeling ?somewhat? (57.5%) or ?very? (21.9%) aware of the special healthcare needs of women with disabilities. Only 17.2%, however, received any information or training on the provision of healthcare to women with disabilities. Eighty-one percent agreed somewhat or strongly that women with disabilities are less likely to receive comprehensive reproductive healthcare. Respondents who provided contraceptive counseling (94.3%) initiated it with women of reproductive age who did not have a disability more frequently than those who had a disability. Finally, only 19.3% felt ?definitely? adequately equipped to manage the pregnancies of women with disabilities. Conclusion: Women with disabilities require reproductive healthcare no less than women without disabilities; however, the evidence consistently identifies disparities. This study suggests that while ob-gyn providers are aware of these issues, they lack adequate training and resources to provide equal care.